PENGARUH PENGANGGURAN, PDRB, DAN PARTISIPASI SEKOLAH TERHADAP KEMISKINAN DI JAWA TIMUR - Galuh Asri, Yohandini Adinda; hanifa, nurul (Jurnal Ekonomika : INDEPENDEN, 2025)
Abstrack Poverty is a problem regarding the welfare of people who are unable to meet their daily needs. This study was conducted to understand the influence of Open Unemployment Rate, GRDP per capita, and School Enrollment Rate on Poverty in 38 Regencies or Cities in East Java Province. The research data comes from BPS for 2018-2023 which was applied and tested with panel data regression analysis using E-Views 12 which shows that partially the Open Unemployment Rate variable has a significant positive effect, GDP per capita has a significant negative effect, and School Enrollment Rate has a significant negative effect on Poverty in East Java Province. As well as the variables Open Unemployment Rate, GRDP per capita, and School Enrollment Rate simultaneously have a significant influence on poverty in 38 districts/cities in East Java.